The description of a new species reveals underestimated diversity in the lichen genus Bulbothrix (Parmeliaceae) in Africa. (9th September 2015) - Unknown
Abstract: Bulbothrix johannis is described as new to science. The species is morphologically similar to the South American Bulbothrix pseudofungicola Benatti & Marcelli but has wider lobes, laminal ciliate isidia which frequently develop into phyllidia, larger cilia and rhizines, and longer ascospores. This epiphytic species occurs fairly frequently in the cloud forests and montane thickets on Réunion Island (Mascarene archipelago). The comparison of B. johannis with morphologically and chemically similar species shows that several different African taxa are currently grouped under the widely used but problematic name B. suffixa (Stirt.) Hale.